APPLICATION OF EXPERT SYSTEM FOR COLOR TELEVISION DIAGNOSE THE DAMAGE USING BORLAND DELPHI 7 - Doheru Anwar; Rahayu Noveandini, Skom, MMSI (Jurnal Sistem Informasi, 2005)
Given the increasingly rapid technology it has developed a technology which is able to adopt processes and modes of human thinking that is Artificial Intelligent technology or artificial intelligence. Artificial Intelligent has a wide variety of applications. In scientific writing, the author discusses about how to create a model of the system (especially damage to the color television). Models made in implementing the system into an application program. Scientific Writing this, also talks about the making of the application using Borland Delphi 7. This application was made aiming to help us diagnose the damage in early television. With this program can make it easier to do what should be the first step in tanggulangi with the damage without having to bring in a technician. TV tracking system damage was made using Delphi programming with Access DBMS for easy distribution.